Douze économistes contre le projet de Constitution européenne - Amable, Bruno; Gadrey, Jean; Hoang-Ngoc, Liêm; Husson, Michel; Lordon, Frédéric; Mazier, Jacques; Palombarini, Stefano; Ramaux, Christophe; Raveaux, Gilles; Saïdi, Aurélien; Sauze, Damien; Théret, Bruno (Paris : L'Harmattan, 2005)
Bibliotheek François Vercammen
Frans
Monografie